Investigating relationships between school context, teacher professional development, teaching practices, and student achievement in response to a nationwide science reform. (May 2018) - Fischer, Christian; Fishman, Barry; Dede, Chris; Eisenkraft, Arthur; Frumin, Kim; Foster, Brandon; Lawrenz, Frances; Levy, Abigail Jurist; McCoy, Ayana
Abstract: Situated in the context of the Advanced Placement curriculum reform in the sciences, this quantitative study validates selected elements of Desimone's (2009) conceptual framework on teacher professional development. Using national data sets with data from 133 336 students and 7434 teachers, multi-level structural equation models indicate that professional development participation and contextual school- and teacher-level factors influence teachers' classroom practices. In turn, aspects of instructional enactments characteristics are significantly, but very weakly, associated with student performance. Thus, this study reinforces calls to provide teachers opportunities for high-quality professional development and suggests to advance research that identifies effective instructional practices. Highlights: Evaluation of a large-scale, top-down, national curriculum and examination reform. Highly valid high-stakes student performance measure. Analysis of school-, teacher-, teaching-, and student-level variables. Teacher professional development can influence classroom instruction. Weak association of some aspects of classroom instruction with student performance.